The minimal pair of sentences as a way of access to morphosyntax for students with hearing loss - Chamorro, Lorena; González del Yerro, Asunción; Roldán, Natividad; de Cos, Manuel (Revista de Investigación en Logopedia, 2017)
The main aim of this study is to evaluate the effects that a program that uses the minimal pair of sentences (the basic strategy used in logogenia) in order to improve the morphosyntactic development of three nine-years-old children who have hearing impairment. Logogenia is a method designed by Radelli in order to facilitate the acquisition of the written language as a first language. An adaptation of the “Escala de Activación de la Competencia Lingüística en el Sordo” (AESACTIV), the “Prueba Evaluación de la Morfosintaxis” (P.E.M.), and the Mean Length of Utterance (MLU) of the answers given to open questions were used to evaluate the morphosyntactic skill. Wilcoxon test showed and statistical increment in pre-post scores obtained in AESACTIV and in P.E.M. Furhermore, children´s answers increased their MLU an average of 1,35 words. Finally, the features of the technique that make the minimal pair of sentences works are analysed, as well as some variables that could affect the effects of the program.
Keywords: Deafness; Hypoacusia; Logogenia; Morphosyntaxis; Nominal Phrase.